Refractory leg ulcers in a patient with 48,XXYY, a rare variant of Klinefelter's syndrome - Läuchli, Severin (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2002)
A case of a 17-year old boy with extensive ulcers on both lower legs is presented. Clinical examination showed an unusually tall stature, obesity and eunuchoid habitus. Chromosomal analysis revealed a karyotype of 48,XXYY, a rare variant of Klinefelter's syndrome (47,XX1ž. After treatment with moist gauze and many recurrences, rapid ulcer healing could be achieved with topicalapplication of Factor XIII. Patients with 48,XXYY seem to be particularly prone to developing extensive leg ulcers. Possible etiologies include chronic venous insufficiency and microvascular disturbances as a consequence of fibrinolytic abnormalities. Differences between Klinefelter's syndrome (47,XX1ž and 48,XXYY are discussed.
Keywords: Adolescenca; Adolescence; Factor XIII; Faktor XIII; Kariotip, določanje; Karyotyping; Klinefelterjev sindrom; Klinefelter's Syndrome; Leg Ulcer; Noga, ulkus; Therapeutic Use